Puerarin ameliorates nonalcoholic fatty liver in rats by regulating hepatic lipid accumulation, oxidative stress, and inflammation - Zhou, Jingxuan; Zhang, Nanhai; Aldhahrani, Adil; Soliman, Mohamed Mohamed; Zhang, Liebing; Zhou, Feng (Frontiers in Immunology, 2022)
Nonalcoholic fatty liver disease (NAFLD) has become one of the public health problems globally. The occurrence of NAFLD is usually accompanied by a series of chronic metabolic diseases, with a prevalence rate is 25.24% among adults worldwide. Therefore, NAFLD seriously affects the quality of life in patients and causes a large economic burden. It has been reported that puerarin has the function of lowering the serum lipids, but due to the complexity of NAFLD, the specific mechanism of action has not been clarified. The aim of this study was to evaluate the preventive or ameliorating effects of two doses of puerarin (0.11% and 0.22% in diet) on high-fat and high-fructose diet (HFFD)-induced NAFLD in rats. The rats were fed with HFFD mixed puerarin for 20 weeks. The results showed that puerarin ameliorated the levels of lipids in the serum and liver. Further exploration of the mechanism found that puerarin ameliorated hepatic lipid accumulation in NAFLD rats by reducing the expression of Srebf1, Chrebp, Acaca, Scd1, Fasn, Acacb, Cd36, Fatp5, Degs1, Plin2, and Apob100 and up-regulating the expression of, Mttp, Cpt1a, and Pnpla2. At the same time, after administration of puerarin, the levels of antioxidant markers (superoxide dismutase, Glutathione peroxidase and catalase) were significantly increased in the serum and liver, and the contents of serum and hepatic inflammatory factors (interleukin-18, interleukins-1β and tumor necrosis factor α) were clearly decreased. In addition, puerarin could ameliorate the liver function. Overall, puerarin ameliorated HFFD-induced NAFLD by modulating liver lipid accumilation, liver function, oxidative stress and inflammation.